Spectrum Comparative Study of Commutation Failure and Short-Circuit Fault in UHVDC Transmission System - Shi-long Chen; Jun-xiang Rong; Gui-hong Bi; Xing-wang Li; Rui-rui Cao (Universitas Ahmad Dahlan, 2014)
When commutation failure occurs in UHVDC transmission system, the transient process of DC voltage and current are similar to grounding short-circuit fault. In order to differentiate them effectively, the paper introduces mathematical morphology methods to analysis the spectrum of transient current. Base on Yunnan-Guangzhou kV UHVDC transmission system, the paper simulates the commutation failure and DC line short-circuit fault under different fault conditions in PSCAD/EMTDC. By modified morphology filter, the transient signal of DC () is decomposed into six scales, and morphological characteristics of aerial mode component of is analyzed under different scales. The simulation results show that when DC line short-circuit faults occurs, wherever in the rectifier side, in the DC transmission line midpoint or in the inverter side, the aerial mode component of have more high frequency weight in and decays gradually; When commutation failures, which are caused by the inverter side AC system single-phase grounding fault, phase to phase fault, three phase grounding fault or the inverter side transformer ratio increased, the aerial mode component of have less frequency weight in.